Plasma arginase-1 as a predictive marker for early transarterial chemoembolization refractoriness in unresectable hepatocellular carcinoma - Xia, Wei-Li; Xu, Shi-Jun; Guo, Yuan; Zhao, Xiao-Hui; Hu, Hong-Tao; Zhao, Yan; Yao, Quan-Jun; Zheng, Lin; Zhang, Dong-Yang; Guo, Chen-Yang; Fan, Wei-Jun; Li, Hai-Liang (Frontiers in Oncology, 2022)
Objective To explore the relationship between plasma arginase-1 (ARG1) and early transarterial chemoembolization (TACE) refractoriness in patients with hepatocellular carcinoma (HCC) and develop nomograms for predicting early TACE refractoriness. Methods A total of 200 patients with HCC, treated with TACE, were included in the study, including 120 in the training set and 80 in the validation set. Pre-treatment enzyme-linked immunosorbent assay was used to detected the plasma ARG1 levels of the patient, and independent predictors of early TACE refractoriness were determined using a multivariate logistic regression model, based on which a predictive model was developed using a nomogram. Results Risk of early TACE refractoriness was negatively correlated with plasma ARG1 levels, and multivariate logistic analysis showed tumour size (OR = 1.138, 95% CI = 1.006-1.288, P = 0.041), multiple tumors (OR=4.374, 95% CI = 1.189-16.089, P = 0.026), platelet count (OR = 0.990, 95% CI = 0.980-0.999, P = 0.036), and plasma ARG1 levels (OR = 0.209, 95% CI = 0.079-0.551, P = 0.002) to be independent prognostic factors for early TACE refractoriness.The AUC value for the nomogram of the training cohort was 0.786 (95% CI = 0.702–0.870), and the validation set AUC value was 0.833 (95% CI = 0.791-0.875).The decision curve analysis suggested that the nomogram had good clinical utility. Conclusion High plasma ARG1 expression was associated with a lower incidence of early TACE refractoriness. The nomogram constructed based on four independent prognostic factors could facilitate an individualised prediction of the incidence of early TACE refractoriness.